Pengaruh Kualitas Produk, Persepsi Harga dan Promosi Terhadap Kepuasan Pelanggan Di OJJU K-Food Mall Kota - Stepen Maridolu Casmira; Ricky Talumantak (Human Capital Development, 2023)
This study aims to determine the effect of Product Quality, Price Perception, Promotion on Customer Satisfaction. Using descriptive quantitative methods using primary data by collecting questionnaire data by processing data using the SPSS application version 24 to obtain the study population are all consumers who came to Ojju K-Food Mall Kota Kasablanka. The sample used was 100 respondents using Purposve sampling technique. So the results of this study partially state the variables of product quality, price perception, promotion have a significant effect on customer satisfaction. Simultaneously product quality, price perception and promotion have a significant effect on customer satisfaction.